Detection of Bacteroides forsythus in Human Subgingival Flora by Using Bacterial Culture and a DNA Probe, and Its Relationship to Periodontal Diseases - Yano, Kazuko (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1997)
The purpose of this investigation was to evaluate the role of Bacteroides forsythus (B. forsythus) in the pathogenesis of periodontal disease. Bacterial cul-ture and DNA probe analysis were performed to detect B. forsythus in subgingival plaque samples obtained from healthy control subjects and patients with adult, and/or early-onset periodontitis. Bac-terial culture and subculture of type strains and clinical isolates of B. forsythus became easier when N-acetylmuramic acid was applied to trypticase soy blood agar at a concentration of 1mg/l. Affirm DP ® (Becton Dickinson, USA) was em-ployed for DNA probe analysis, and this system was found to be capable of detecting more than105 bacterial cells. After the standard methods of bacterial culture and the DNA probe method were established, the prevalence of B. forsythus in subgin-gival plaque from various types of periodontal disease was investigated. The results showed that B. forsythus was seldom detected in the gingival sulcus in the healthy control group, but was detect-ed at a much higher ratio in the pockets ofperi-odontitis group by both methods. Furthermore, the prevalence and total cultivable number of B. forsy-thus weresignificantly correlated with probing pocket depth, bleeding on probing, and degree of bone loss, suggesting that B. forsythus is plays a large role in the pathogenesis ofperiodontitis